2021
DOI: 10.1097/rhu.0000000000001775
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Patients With ANCA-Associated Vasculitides in a Colombian Hospital

Abstract: Background/Objective: Antineutrophil cytoplasmic antibody-associated vasculitides (AAVs) are uncommon systemic autoimmune diseases, of which few reports exist in Latin America. Our aim was to examine AAV evaluated in a high-complexity hospital in southwestern Colombia, with emphasis in severe forms. Methods:A medical records review study of 67 patients was performed, and data were collected from electronic registries. Moderate and severe AAVs were defined as the presence of life-threatening complications, unfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There was a significant female preponderance, noted in other pediatric studies as well [ 5 , 9 , 10 , 27 ]. Studies from Latin America have also observed a female predominance in adult ANCA associated vasculitis [ 14 , 29 ]. Meanwhile in several adult studies, AAV has been noted to be more frequent in males than in females [ 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant female preponderance, noted in other pediatric studies as well [ 5 , 9 , 10 , 27 ]. Studies from Latin America have also observed a female predominance in adult ANCA associated vasculitis [ 14 , 29 ]. Meanwhile in several adult studies, AAV has been noted to be more frequent in males than in females [ 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple organ system involvement is common in AAV, especially the lung and kidney, with resultant alveolar hemorrhage, acute renal failure, and a high risk of death [2,3]. Due to differences in clinical manifestations of AAV, many patients have acute onset and rapid progression of the disease, which often brings di culties to disease assessment [4]. Erythrocyte sedimentation rate (ESR), C reactive protein (CRP) levels, and Birmingham Vasculitis Activity Score (BVAS), as well as other biomarkers are commonly used to evaluate disease activity [5].…”
Section: Introductionmentioning
confidence: 99%